Pelatihan Penulisan Artikel dan Publikasi Jurnal bagi Mahasiswa dan Mahasiswi di Kota Tangerang Selatan - Jakariah Jakariah; Syamruddin Syamruddin; Ahmad Yani Nasution (Indonesian Journal of Society Engagement, 2025)
This Community Service (PkM) was carried out with the aim of providing understanding and provisions to male and female students in South Tangerang City regarding article writing and easy tips for publication in journals. Thus, male and female students are able to create quality articles that can penetrate scientific journals. The PkM method includes partner situation analysis, problem identification, problem-solving solutions, preparation for implementation, implementation of activities as well as evaluation, reporting, and output. The results of this PkM show an increase in participant knowledge, ability to draft scientific articles, use citation tools, proficiency in using the Mendeley Application, and ability to submit to journals. Then, interest in publications increases and the strengthening of academic networks is increasingly numerous. Abstrak Pengabdian kepada Masyarakat (PkM) ini dilaksanakan bertujuan untuk memberikan pemahaman dan bekal kepada mahasiswa dan mahasiswi yang ada di  Kota Tangerang Selatan mengenai penulisan artikel dan tips mudah untuk publikasi pada jurnal. Dengan demikian mahasiswa dan mahasiswi mampu membuat artikel yang berkualitas sehingga bisa tembus pada jurnal ilmiah. Metode PkM ini meliputi analisis situasi mitra, identifikasi masalah, solusi pemecahan masalah, persiapan pelaksanaan, pelaksanaan kegiatan serta evaluasi, pelaporan, dan luaran. Hasil PkM ini menunjukkan adanya peningkatan pengetahuan peserta, mampu dalam menyusun draf artikel ilmiah, penggunaan alat bantu sitasi, mahir dalam menggunakan Aplikasi Mendeley, dan mampu melakukan submission pada jurnal. Kemudian minat publikasi meningkat dan penguatan jejaring akademik yang semakin banyak. Kata Kunci: pelatihan; artikel; publikasi; jurnal